Clinical Research: Auditory Stimulation in the Disorders of Consciousness - Zhu, Jiajie; Yan, Yifan; Zhou, Wei; Lin, Yajun; Shen, Zheying; Mou, Xuanting; Ren, Yan; Hu, Xiaohua; Di, Haibo (Frontiers in Human Neuroscience, 2019)
Due to the complex situation of disorder of consciousness (DOC) patients, the assessment of conscious state of these patients has been a great challenge for a long time[1]. At present, the main clinical diagnostic method to assess the conscious state of the DOC is the relevant behavior scale like Coma Recovery Scale-Revised(CRS-R). In this article, we will focus on auditory stimulation and select some representative auditory stimulus, calling names and music stimulation, to discuss the function and application of the auditory stimulus in patients with DOC and provide guidance for future research.